2019
DOI: 10.1186/s12967-019-2083-0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue diagnosis during colorectal cancer surgery using optical sensing: an in vivo study

Abstract: Background In colorectal cancer surgery there is a delicate balance between complete removal of the tumor and sparing as much healthy tissue as possible. Especially in rectal cancer, intraoperative tissue recognition could be of great benefit in preventing positive resection margins and sparing as much healthy tissue as possible. To better guide the surgeon, we evaluated the accuracy of diffuse reflectance spectroscopy (DRS) for tissue characterization during colorectal cancer surgery and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Relevant biochemical and structural differences for CRC detection. From a clinical perspective, biomolecular changes probed by optical techniques can potentially obviate the need for multiple biopsies or polypectomies of normal mucosa as well as identify sessile serrated polyps, which may be difficult to recognize during colonoscopy at times [7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The potential of optical spectroscopy for colorectal cancer (CRC) detection in ex vivo specimens or in vivo during colonoscopy has been evaluated for superficial tissues (small SDD probes) in several wavelength ranges [39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Relevant biochemical and structural differences for CRC detection. From a clinical perspective, biomolecular changes probed by optical techniques can potentially obviate the need for multiple biopsies or polypectomies of normal mucosa as well as identify sessile serrated polyps, which may be difficult to recognize during colonoscopy at times [7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The potential of optical spectroscopy for colorectal cancer (CRC) detection in ex vivo specimens or in vivo during colonoscopy has been evaluated for superficial tissues (small SDD probes) in several wavelength ranges [39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of tissue type and thickness of the first two layers is incredibly valuable information and can be used to provide intra-operative guidance for surgeons in order to achieve accurate resection margins and preserving healthy tissue as much as possible. In addition, Baltussen et al examined the influence of tumor depth from the measurement surface on the classification accuracy when assuming one homogeneous tissue volume 33 . They showed that the classification accuracy drops from a tumor depth of 1.5 mm, using a fiber distance of 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the use of frozen sections did not seem to improve the accuracy. Promising devices and methods to improve detection of R1 marigins per-operatively could be the use of bevacizumab-800CW by back-table and intra-operative fluorescence-guided imaging, computer navigation-assisted surgery or diffuse reflectance spectroscopy [41,42]…”
Section: Discussionmentioning
confidence: 99%